PROGRESSIVE DECOMPOSITION OF C-C BONDS IN PROPANE-BUTANE MIXTURES IN THE PRESENCE OF NON-METALLIC MODIFIED MESOPORUS ZEOLITE CATALYSTS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Light olefins, including ethylene, propylene, butenes, and butadienes, are the main building blocks used in the chemical industry to produce polymers, solvents, construction, synthetic fibers, etc. [1-6]. Ethylene can be used to produce polyethylene, polyvinyl chloride, etc. Due to the increasing demand for polyethylene, ethylene production is expected to increase from 169 million tons in 2017 to 230 million tons in 2023. Propylene is used to produce polypropylene, acrylonitrile , etc. [ 7-11 ]. Annual butene production is around 132 million tons, among which isobutene is mainly used as a raw material for the production of alkylates [ 12-17 ].